Mobilização de saberes docentes de uma professora pedagoga nos anos iniciais do ensino fundamental: um estudo de interações discursivas em aulas de Ciências - Rafael Alves Ferreira Almeida (2017)
In this research we investigated how an elementary teacher with little experience in science teaching mobilized in science lessons her knowledge about teaching 1st graders how to rea and to write. Based on elements of an ethnographic perspective and on discourse studies, weanalyzed video records from a database composed of Portuguese and Scice lessons from 1st through 3rd grade. We focused our analysis on the first semester of the first year, considering that this period would be the moment in which literacy events are more frequent in Portuguese lessons, and, at the same time, children are introducted to school science. Therefore, this period has the potential to make it possible to describe teachers actions and mobilization of teachers knowledge for teaching science. Based on preliminary analyzes of the videos and discussions in the literature researches on teacher education and on classroom discourse, we have constructed an analytical perspective structured around three dimensions that reflect the particularities of the teacher's practice: i) how the teacher deals with doubt and with possibility of multiple answers; ii) how the teacher mobilizes students talk in adiscussion; and, iii) how the teacher deals with error and accuracy in students answers. In order to analyze actions of the teacher in relation to these dimensions, we have constructed telling cases in Portuguese and in Science lessons that make conspicuous the theoretical relations existing between her actions, and the mobilization of literacy knowledge for science teaching. By contrasting teachers actions in events in Portuguese and in Science lessons we identified continuities and ruptures in her practice. Our results evidenced what the teacher knew and was able to accomplish in science lessons, contradicting a perspectivethat emphasizes limitations of these professionals in teaching science. Our results indicated the importance of initiatives that seek to understand what elementary teachers actually know and how this knowledge enables or not them to promote science learing at elementay school. These type of studies can contribute to advances in preservice and in-service Teacher Education.